Comprehensive Study of Gokshura (Tribulus terrestris Linn.) in Ayurvedic Literature with Special Reference to Mutrakricchra - Gautam, Priyanka; Bairwa, Omprakash; Yadav, Rajkumar; Singh, Anil Kumar (International Research Journal of Ayurveda & Yoga, 2023)
Ayurveda, the science of life has many principles, which are universally applicable and have potential to help humanity to live healthy and happy life. We have always preferred Ayurvedic lexicons for detailed knowledge of any medicinal plants or health ailments and different disorders. The Mutrakricchra word comes under the diseases of Mutravaha Strotas. Mutrakricchra – “Dukhen mutra pravritti” means difficulty while micturition or dysuria is the main symptom of Mutrakricchra roga. There are so many medicinal plants and formulations which are used for the treatment of Mutrakricchra roga (urinary tract infection). Gokshura (Tribulus terrestris Linn.) is one of the important medicinal plants that have been used single or in combined form, effectively used by many Ayurvedic practitioners from very beginning. In this present study, we are making efforts to arrange chronologically ayurvedic literature review of Gokshura (Tribulus terrestris Linn.) in reference to treat mutrakricchra roga (urinary tract infection). In this comprehensive study, we found that Gokshura (Tribulus terrestris Linn.) has been defined single or in various pharmacological compound preparations in reference to mutrakricchra roga. This detailed review of Gokshura (Tribulus terrestris Linn.) will be helpful for researcher in future.